Uncertainty in Loading and Control of an Active Column Critical to Buckling - G.C. Enss; R. Platz; H. Hanselka (Shock and Vibration)
Buckling of load-carrying column structures is an important design constraint in light-weight structures as it may result in the collapse of an entire structure. When a column is loaded by an axial compressive load equal to its individual critical buckling load, a critically stable equilibrium occurs. When loaded above its critical buckling load, the passive column may buckle. If the actual loading during usage is not fully known, stability becomes highly uncertain.